The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1099/jmm.0.022707-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent genotypes of meticillin-resistant Staphylococcus aureus: report from Pakistan

Abstract: Meticillin-resistant Staphylococcus aureus (MRSA) is a major nosocomial pathogen in Pakistan and is emerging in the community. This is one of the first reports of the prevalent genotypes of MRSA in both hospital and community settings in Pakistan. Isolates collected in 2006-2007 were characterized by PFGE, staphylococcal cassette chromosome mec (SCCmec) typing and multilocus sequence typing (MLST). PFGE identified nine pulsotypes, the majority of isolates belonging to pulsotypes A (n570) and B (n538), which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 48 publications
(46 reference statements)
5
17
0
1
Order By: Relevance
“…In previous studies of MRSA and MSSA strains in the cities of Isfahan and Tehran the majority of MRSA isolates belonged to ST239 [25]. The high prevalence of ST239 has been documented from many Asian countries especially India, Pakistan, Vietnam, Thailand, Taiwan, China, Sri Lanka, and Singapore [27]. In accordance with other studies, our MRSA isolates with ST239 belonged to SCCmec types II and III, with similar antibiotic resistance and virulence patterns [22].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In previous studies of MRSA and MSSA strains in the cities of Isfahan and Tehran the majority of MRSA isolates belonged to ST239 [25]. The high prevalence of ST239 has been documented from many Asian countries especially India, Pakistan, Vietnam, Thailand, Taiwan, China, Sri Lanka, and Singapore [27]. In accordance with other studies, our MRSA isolates with ST239 belonged to SCCmec types II and III, with similar antibiotic resistance and virulence patterns [22].…”
Section: Discussionsupporting
confidence: 89%
“…According to MLST genotyping, S. aureus strains have been documented to be highly clonal and the most of the strains belong to a limited number of closely related genotypes. Literature have shown that CC8 (Iberian clone, Brazilian clone, Archaic clone), CC5 (New York/Japanese clone, Pediatric clone) and CC22 (epidemic MRSA-15) belong to epidemic MRSA (EMRSA) clones with global distribution in hospitals [27]. In accordance with our study, CC8-V was found as predominant clone in study conducted in Armenia [8].…”
Section: Discussionsupporting
confidence: 89%
“…In Australia, it is a common cause of hospital-acquired infection in the East coast states, and large outbreaks in the 1980s were attributable to this strain [155]. Furthermore, ST239-MRSA-III has also been reported in Argentina [185], Brazil [186]; [187], Chile [185], Egypt (isolates courtesy of M. Kamal El Din, Cairo), India [104], Korea [171], Malaysia [172], Mongolia [168], New Zealand [174], Pakistan [188], Paraguay [42], Russia [189], South Africa [73], Thailand [176] and Uruguay [185]. The reference strain ATCC33592, recovered in a hospital in New York [190], belongs also to ST239-MRSA-III.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] However, MRSA is not only the problem in hospital but also a serious problem for community due to emergence of the community acquired MRSA. 4 Health care workers(HCWs) colonized with MRSA may carry these virulent hospital strains in their nose and skin and may transmit these organisms to the community creating a more dreadful situation.…”
Section: Introductionmentioning
confidence: 99%